Cephalometric Norms-based on Steiner’s Analysis on Young Adults of Tamil Nadu Population - Evan. A. Clement; Navaneetha Nambi; Anusha Sreedharan; Dharmisha; Arshitha Ramesh (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aim-The purpose of the study was to establish skeletal and dental parameters for Tamil Nadu young adults using Steiner’s analysis and comparing it with Caucasians, as well as other racial groups. Materials &Methods- A study of 70 south Indian young adults (35 male and 35 female) within the age range of 18-28 years with acceptable profile and occlusion was selected for the study and assessed using Steiner’s analysis. Results- The Tamil Nadu population showed a more skeletally protrusive maxilla, dentally proclined and forwardly positioned upper and lower incisor, it also exhibited a horizontal growth pattern when compared with Caucasians norms. The Tamil Nadu male samples reported a protrusive skeletal and dental pattern when compared to female samples. Conclusion-The result of the study supports the fact that the norms and standards of one racial group could not be used without modification for other racial groups and each different racial group would have to be treated according to its individual characteristics. A case of malocclusion needs to be treated based on the individual merits and demerits of that case and not based on a template of norms derived from mean values of select subject groups with ideal occlusion and proportion.